2021
DOI: 10.1002/onco.13746
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of the 4-Item Geriatric Depression Scale for Depression Screening in Older Patients with Cancer: The ELCAPA Cohort Study

Abstract: Background. In older patients with cancer, depression is difficult to assess because of its heterogeneous clinical expression. The 4-item version of the Geriatric Depression Scale (GDS-4) is quick and easy to administer but has not been validated in this population. The present study was designed to test the diagnostic performance of the GDS-4 in a French cohort of older patients with cancer before treatment. Materials and Methods. Our cross-sectional analysis of data from the Elderly Cancer Patient cohort cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
1
0
3
Order By: Relevance
“…Entre as dez nacionalidades citadas nos estudos (Turquia, Índia, Itália, Irlanda, Croácia, Estados Unidos, Suécia, Alemanha, Japão, França), evidencia-se diversas realidades e situações específicas e singulares de cada nação/cultura. Ademais, cabe ressaltar que é de suma importância que os países reorganizem sua forma de prover assistência holística aos pacientes com câncer, estruturando principiante ações de prevenção e promoção em saúde mental (YANG et al, 2017;MALLET et al, 2018;LAFONT et al, 2021). SAXENA et al, 2018;ESSER et al, 2019;AKECHI et al, 2020 Câncer de cabeça e pescoço (boca, língua, faringe, laringe) MALLET et al, 2018;SAXENA et al, 2018;ANUK et al, 2019;ESSER et al, 2019;AKECHI et al, 2020;HARROLD et al, 2020;SALM et al, 2021Câncer ósseo SAXENA et al, 2018Melanoma ZHU et al, 2017ESSER et al, 2019;AKECHI et al, 2020;SALM et al, 2021Câncer hematológico ZHU et al, 2017ESSER et al, 2019;AKECHI et al, 2020;LAFONT et al, 2021;SALM et al, 2021Linfoma AKECHI et al, 2020Mieloma múltiplo AKECHI et al, 2020Câncer de tireoide ESSER et al, 2019AKECHI et al, 2020Câncer de pulmão ZHU et al, 2017SAXENA et al, 2018;ANUK et al, 2019;ESSER et al, 2019;AKECHI et al, 2020;HARROLD et al, 2020;SALM et al, 2021Câncer de mama YANG et al, 201...…”
Section: Resultsunclassified
“…Entre as dez nacionalidades citadas nos estudos (Turquia, Índia, Itália, Irlanda, Croácia, Estados Unidos, Suécia, Alemanha, Japão, França), evidencia-se diversas realidades e situações específicas e singulares de cada nação/cultura. Ademais, cabe ressaltar que é de suma importância que os países reorganizem sua forma de prover assistência holística aos pacientes com câncer, estruturando principiante ações de prevenção e promoção em saúde mental (YANG et al, 2017;MALLET et al, 2018;LAFONT et al, 2021). SAXENA et al, 2018;ESSER et al, 2019;AKECHI et al, 2020 Câncer de cabeça e pescoço (boca, língua, faringe, laringe) MALLET et al, 2018;SAXENA et al, 2018;ANUK et al, 2019;ESSER et al, 2019;AKECHI et al, 2020;HARROLD et al, 2020;SALM et al, 2021Câncer ósseo SAXENA et al, 2018Melanoma ZHU et al, 2017ESSER et al, 2019;AKECHI et al, 2020;SALM et al, 2021Câncer hematológico ZHU et al, 2017ESSER et al, 2019;AKECHI et al, 2020;LAFONT et al, 2021;SALM et al, 2021Linfoma AKECHI et al, 2020Mieloma múltiplo AKECHI et al, 2020Câncer de tireoide ESSER et al, 2019AKECHI et al, 2020Câncer de pulmão ZHU et al, 2017SAXENA et al, 2018;ANUK et al, 2019;ESSER et al, 2019;AKECHI et al, 2020;HARROLD et al, 2020;SALM et al, 2021Câncer de mama YANG et al, 201...…”
Section: Resultsunclassified
“…Las razones de verosimilitud positiva y negativa fueron 8.2 y 0.11, y el AUROC fue 92%. Al considerar el subconjunto de pacientes con datos sobre todas las medidas de depresión, los valores de sensibilidad y especificidad fueron, respectivamente, ≥90 % y ≥72 %, los cocientes de probabilidad positivos y negativos fueron, respectivamente, ≥3,4 y ≤ 0,11, y el AUROC fue ≥91% (Lafont et al, 2021) Mientras que en estudio de casos y controles en el Líbano al incluir a 500 pacientes mayores de 60 años (250 que vivían dentro y 250 fuera de una residencia de ancianos).…”
Section: Discussionunclassified
“…La sensibilidad y especificidad del GDS-4 para detectar depresión diagnosticada por un médico es, respectivamente, 90% y 89%. Concluyendo que el GDS-4 parece ser una herramienta clínicamente relevante y fácil de usar para la detección sistemática de la depresión en pacientes mayores (Lafont et al, 2021). Dentro de este orden de ideas, un estudio realizado sobre la precisión diagnóstica de diversas formas de escala de depresión geriátrica para el cribado de la depresión en adultos mayores, se encontró que todas las formas de Geriatric Depression Scale (GDS) muy útiles para detectar la depresión entre los ancianos con mayor sensibilidad y especificidad.…”
Section: Introductionunclassified
“…The ELPACA cohort study recently examined the French version of the GDS-4 as a short-item screening tool for evaluating the risk of depression [24]. The authors concluded that this French GDS-4 appeared to be a clinically relevant, user-friendly tool for routine screening for depression in older patients with cancer.…”
Section: Discussionmentioning
confidence: 99%